Anthropometric and Quality-of-Life Parameters in Acute Intermittent Porphyria Patients. Issue 30 (July 2015) - Jiménez-Monreal, Antonia M; Murcia, MAntonia; Gómez-Murcia, Victoria; Bibiloni, Maria del Mar; Pons, Antoni; Tur, Josep A.; Martínez-Tomé, Magdalena; Sanket, Patel.
<x xml:space="preserve">Abstract</x> Abstract The porphyrias are a group of rare metabolic disorders. The incidence and prevalence are low because the acute intermittent porphyria (AIP) is rare. Our aim was to assess the use of anthropometric and quality-of-life parameters in porphyric patients in order to identify predictor factors that might help in characterizing AIP patients. Sixteen AIP patients from Murcia (Spain) were recruited from local health centers in 2008 and 2009. A control group of 16 healthy people was established. Body composition was assessed by bioelectrical impedance analysis (BIA) and anthropometric measurements: body weight; height; knee-heel height; waist, hip, upper arm and calf circumferences (CCs); biacromion and biiliac diameters; bicondylar and biepicondylar width; and triceps, subscapular, supraspinale, and calf skinfold thickness. Anthropometric indicators were obtained from anthropometric measurements. A quality-of-life evaluation was carried out using the EuroQol-5D (EQ-5D) questionnaire and Barthel and Katz indexes. Significant differences in means were tested by unpaired Student t test. Group differences in anthropometric measurements were tested with a 2-way analysis of variance (group × condition: age group, overweight, and adiposity degree). Relative frequencies were obtained for noncontinuous variables. Significant differences in prevalence were calculated by means of χ2. AIP patients showed statistically significant differences in terms of knee-heel height, biiliac diameter, CC, triceps skinfold thickness, BIA, ponderal index, endomorphy, and ectomorphy. Only 1 quality-of-life indicator, visual analog scale, in the EQ-5D questionnaire showed significant differences between porphyric and control groups. Some anthropometric parameters and the EQ-5D questionnaire could be used to appreciate the presence or follow the evolution of the disease in AIP patients.